Memoria storica, riforma del teatro e identità nazionale nel ciclo di tragedie romane di Antonio Conti - Simone Forlesi (Caietele Echinox, 2023)
This essay aims to analyze the presence of historical memory in Antonio Conti’s poetical and theoretical reflection. Through his cycle of Roman tragedies, he staged some salient moments of Roman history which illustrated the transition from the monarchy to the republic, and from the republic to the empire. In the framework of the theatrical reform inaugurated at the beginning of the 18th century by Scipione Maffei’s Merope, Conti’s dramaturgical and theoretical work constitutes an extremely important contribution , starting from the tragedies’ ponderous paratexts, where the author gradually establishes the need for a national theatre, following the English and French models, while being centered exclusively on the events of Roman history.